Analisis Framing "Aksi Bela Islam" sebagai Dakwah Islam di Riau Pos (A Framing Analysis of "Islam Defense Action" as Islamic Dakwah on Riau Pos Newspaper) - Muhd Ar. Imam Riauan; Abdul Aziz; Nurman Nurman (Jurnal Dakwah Risalah, 2020)
This article aims to examine how the representation of Action to Defend Islam in Riau Pos newspaper. Action to Defend Islam shows peaceful action of Muslims which contains messages of da'wah. This study uses qualitative content analysis by Robert N. Entman's model. The news examined was published during the action on 14 October 2017 until 5 May 2017 in the Riau Pos newspaper. The results of this study shows that the Action to Defend Islam contains the message of da'wah to carry out mass actions in peace and ordered; action to defend Alquran; action to obey the leader; and action to strengthen brotherhood among Muslims.